A movement generation algorithm for FE Human Body Models. Issue 1 (15th March 2018) - Martynenko, Oleksandr; Schmitt, Syn; Bayer, Alexandra; Blaschke, Julian; Mayer, Christian
Abstract: Finite element (FE) method simulations are increasingly used for the development in the area of vehicle safety nowadays. Highly detailed virtual mechanical and human body models (HBMs) available for use in connection with the increase of the processors performance and algorithms efficiency, give engineers the opportunity to simulate not only the car crash event itself but also a so‐called pre‐crash phase. This is important for the design and improvement of steering‐assist and autonomous driving systems, through the assessment of active occupant behaviour during the impact avoidance or any other complex driving manoeuvres. To enable adequate evaluation of such simulations, virtual Active Human Body Models (AHBMs) should be established, capable to not only reproduce reflex human reactions but also for simulations of human movements. This study investigates the applicability of a forward dynamics movement generation algorithm for the FE HBMs, presents first results and outlines questions, need to be solved in future to do such simulations in a robust and time effective way. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)